2019
DOI: 10.3389/fpls.2019.01162
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of UDP-Glucose Sterol Glucosyltransferases Enhances Arabidopsis Resistance to Botrytis cinerea

Abstract: Free and glycosylated sterols are both structural components of the plasma membrane that regulate their biophysical properties and consequently different plasma membrane-associated processes such as plant adaptation to stress or signaling. Several reports relate changes in glycosylated sterols levels with the plant response to abiotic stress, but the information about the role of these compounds in the response to biotic stress is scarce. In this work, we have studied the response to the necrotrophic fungus Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…Collectively, these studies suggest that SGs induce T cell proliferation, direct Th1 cell differentiation, and induce earlier host recognition leading to rapid recruitment of innate immunity. However, the majority of the vaccination studies utilizing SGs have been performed using plants ( Thuan et al., 2013 ; Singh et al., 2016 ; Castillo et al., 2019 ) or purified SGs as a standalone compound prior to infection to induce a protective immune response, not as a simultaneous immunoadjuvant present during the active infection stage ( Lee and Han, 2006 ; Lee et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these studies suggest that SGs induce T cell proliferation, direct Th1 cell differentiation, and induce earlier host recognition leading to rapid recruitment of innate immunity. However, the majority of the vaccination studies utilizing SGs have been performed using plants ( Thuan et al., 2013 ; Singh et al., 2016 ; Castillo et al., 2019 ) or purified SGs as a standalone compound prior to infection to induce a protective immune response, not as a simultaneous immunoadjuvant present during the active infection stage ( Lee and Han, 2006 ; Lee et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…6). On the contrary, PDF1.2 would be induced by B. cinerea to activate JA pathway for increasing the resistance in Arabidopsis [28]. In addition, a similar expression pattern was observed for PR4, which is another JAresponsive gene of the ERF branch and its expression levels could be induced by necrotrophic pathogen [52], but was also decreased in pri-miR482b OE plants compared to WT.…”
Section: Discussionmentioning
confidence: 58%
“…The jasmonic acid-mediated defense pathway has an important role in plant resistance against necrotrophic pathogens [48]. There are two distinct branches in Arabidopsis JA pathway including ethylene response factor (ERF) branch and the MYC branch [28]. The ERF branch of the JA pathway is typically activated upon infection by necrotrophic pathogens [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that silencing SGTs resulted in a positive feedback regulation of withanolide biosynthesis, leading to reduced biotic stress tolerance. In conflict with these results, a 2019 study by Castillo and colleagues [81] reported that inactivation of the SGT enzymes in Arabidopsis plants enhanced the resistance to the necrotrophic fungus Botrytis cinerea. The authors showed that the mutant strain of Arabidopsis that cannot produce SGs was more resistant to infection with B. cinerea due to an increase in plant stress response factors to combat the infection.…”
Section: Plantsmentioning
confidence: 97%